Automatic dual axis solar tracking apparatus, system and method thereof - Shafie, Suhaidi; Ahmad, Salsabila; Ab Kadir, Mohd Zainal Abidin; Mohd Radzi, Mohd Amran (2013)
The present invention relates to a dual axis solar tracking apparatus (300), system and method thereof for use in electrical power generation. The dual-axis solar tracking apparatus (300) comprises a frame structure and a base connected to the frame structure. Preferably, the dual-axis solar tracking apparatus (300) further comprises a plate (301), assembly member (304), auxiliary member, and caster (204). The method of tracking paths of the sun using a dual-axis solar tracking apparatus (300) is preferably based on local time and/or date. The present invention is capable to provide rotations at least by one degree with respect to a first and second axis.